Modeling and Simulation of Hydrogen Gas Production Process from Natuna Natural Gas - Laba Wuwur, Gerry Septian; Budhi, Yogi Wibisono (ITB Graduate School Conference, 2025)
The Natuna gas field in Indonesia holds significant natural gas reserves, estimated at 222 trillion standard cubic feet (TSCF), with high CO2 content. Dry reforming of methane (DRM) and steam methane reforming (SMR), followed by the reverse water gas shift reaction (RWGSR), are key processes for converting natural gas into syngas and hydrogen. However, carbon formation and catalyst sintering at high temperatures challenge DRM implementation. This study presents a one-dimensional plug flow reactor (PFR) model under steady state conditions using a pseudo-homogeneous mass balance approach. Simulations were conducted using FlexPDE V.7, incorporating mass balance with a Ni/γ-Al2O3 catalyst and Langmuir-Hinshelwood-Hougen-Watson (LHHW) kinetics. The feed gas composition consisted of 70% CO2 and 30% CH4, the gas space time was 1 s. The reactor dimensions were 0.10 m in length and 0.04 m in diameter. Results indicate that a H2O flow rate of 0.3 mol/s at temperatures 900 °C effectively reduces carbon formation without promoting methane cracking. Optimal CH4 and CO2 conversion occurs at 700–1000 °C and pressures of 5–10 bar. The most stable H2/CO ratio is achieved with H2O flow rates of 0.3–0.5 mol/s. Proper H2O addition enhances DRM and SMR efficiency, improving syngas production from Natuna natural gas.